BENIKO AND BIALOBREZSKIE – INDUSTRIAL HEMP VARIETIES IN LITHUANIA (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
The biometrical indices of two hemp (Cannabis sativa L.) varieties of Polish origin – Beniko and Bialobrezskie – sown at different rates (40; 55 and 70 kg ha-1) have been investigated at the Upytė Research Station of LIA in 2006. The data from 2006 led to draw conclusion that plants of industrial hemp varieties of Beniko and Bialobrzeskie could be successfully grown in Lithuania. Hemp produced enough high amount of green (up till 42.95 t ha-1) and dry (up till 15.27 t ha-1) biomass. Plants of Beniko were more productive than plants of Bialobrzeskie. The tendencies of higher green and dry biomass were noticed in the plots of lower density. Seed rate had significant influence on crop density. Seed rate (crop density) had significant effect on crop weediness.